Improving Educational Quality through Teacher Mentoring and Community Collaboration - Iqbal, Khurshed (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
This community service project was conducted to address the persistent challenge of improving educational quality through a more participatory and sustainable approach that combines teacher mentoring and community collaboration. The main objective was to enhance teachers’ pedagogical competence and strengthen community involvement in the learning process. Using the Participatory Action Research (PAR) method, the program was implemented over six months at SD Negeri 2 Nanga Jetak, Kabupaten Sintang, involving teachers, school leaders, and local community representatives as active partners. Data were collected through interviews, observations, and questionnaires, then analyzed using descriptive statistics, correlation tests, and thematic analysis. The results showed a significant improvement in teachers’ instructional quality, reflective practice, and community participation, with a positive correlation (r = 0.76, p < 0.01) between mentoring intensity and teacher performance. The study concludes that integrating mentoring with community collaboration effectively builds professional capacity and strengthens social partnerships in education. This project contributes a replicable and context-sensitive model for sustainable school improvement and community empowerment.